Surface hardness prediction based on cutting parameters in turning of annealed AISI 1020 steel (2017)
The influence of various cutting parameters, cutting speed (Vc), feed rate (f), and depth of cut (d) on the surface hardness developed by turning annealed AISI 1020 steel using carbide insert tools was investigated. It was shown from the measured results that hardness increases with the increase in all the studied parameters. An analysis of variance (ANOVA) was employed to determine the contributions of each parameter on the response variable. From the results, it was found that cutting speed has the most significant role in producing surface hardness (69.2 %) followed by feed rate (24.4 %), while the depth of cut has the lesser effect (6.4%). Finally, a simple equation is proposed, for the prediction of the values of surface hardness, which accounts for the effects of process parameters.